Cambridge Primary English Activity Book - 4 - Sally Burt; Debbie Ridgard (United Kingdom CAMBRIDGE UNIVERSITY PRESS, 2014)
Cambridge Primary English is a flexible, endorsed course written specifically to support Cambridge International Examinations' curriculum framework (Stages 1-6). This write-in Activity Book includes the following features. Activities which support, enrich and reinforce the core teaching in the Learner's Book, using the same themes and texts to enhance comprehension. Activities which are designed to build, practise and consolidate the reading and writing skills of all learners. Further activities and games targeting specific grammar and language points, extra writing and spelling activities.
Keywords: TR - PY - Language -- TR - PY - Language